Forum for scientific method in biology: transcript - Carusi, A; Rodriguez, B; Wakefield, J; Burrage, K; Keller, E; Goodwin, B; Maini, P; Margulis, L; Noble, D; Terrar, D; Trefethen, A; Werner, E (2009)
A transcript of an event held at the Oxford e-Research Centre on 25th February, 2009. The group included computational, mathematical and experimental biologists, philosophers and historians of science discussing issues relating to modelling, simulation, experiment, quantitative and qualitative approaches, institutional aspects of research, collaboration, and education, among other topics.